2017
DOI: 10.1038/srep44417
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory interneuron circuits at cortical and spinal levels are associated with individual differences in corticomuscular coherence during isometric voluntary contraction

Abstract: Corticomuscular coherence (CMC) is an oscillatory synchronization of 15–35 Hz (β-band) between electroencephalogram (EEG) of the sensorimotor cortex and electromyogram of contracting muscles. Although we reported that the magnitude of CMC varies among individuals, the physiological mechanisms underlying this variation are still unclear. Here, we aimed to investigate the associations between CMC and intracortical inhibition (ICI) in the primary motor cortex (M1)/recurrent inhibition (RI) in the spinal cord, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 56 publications
3
33
1
Order By: Relevance
“…This is not surprising given the dynamic and rhythmic nature of gait, which will elicit rhythmic oscillations in all sensori-motor networks that contribute to the activation of the muscles. Brain imaging studies also confirm that sensory feedback mechanisms are responsible for a very significant part of the activation of cortical motor areas during locomotion (Christensen et al 2000;Promjunyakul et al 2015) and local inhibitory interneurons have been shown to modulate EEG-EMG coherence in a sustained isometric contraction (Matsuya et al 2017).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This is not surprising given the dynamic and rhythmic nature of gait, which will elicit rhythmic oscillations in all sensori-motor networks that contribute to the activation of the muscles. Brain imaging studies also confirm that sensory feedback mechanisms are responsible for a very significant part of the activation of cortical motor areas during locomotion (Christensen et al 2000;Promjunyakul et al 2015) and local inhibitory interneurons have been shown to modulate EEG-EMG coherence in a sustained isometric contraction (Matsuya et al 2017).…”
Section: Discussionmentioning
confidence: 75%
“…) and local inhibitory interneurons have been shown to modulate EEG‐EMG coherence in a sustained isometric contraction (Matsuya et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…They thus reported a positive correlation between the amount of corticospinal coherence between Cz EEG and SOL and the level of recurrent inhibition indicating that spinal mechanisms indeed modulate the corticomuscular coherence. In the present study, the source of the oscillatory activity cannot be isolated and both cortical and spinal mechanisms most likely contribute and modulate the observed coherence (Matsuya et al 2017).…”
Section: Discussionmentioning
confidence: 81%
“…CMC is a well-known concept in the neurorehabilitation field, defined as the coherence function between an electroencephalographic (EEG) and an electromyographic (EMG) signal, well characterized in boh healthy subjects [1] and those affected by different kinds of motor-related diseases.…”
Section: Introductionmentioning
confidence: 99%